2008
DOI: 10.1177/0269881108098809
|View full text |Cite
|
Sign up to set email alerts
|

Lamotrigine as an augmentation agent in treatment-resistant obsessive-compulsive disorder: a case report

Abstract: Obsessive-compulsive disorder (OCD) is a relatively common, often chronic and disabling disorder with high rates of partial and/or absent response to standard, recommended treatments. We report a case of treatment-resistant OCD that was successfully treated with a pharmacological augmentation of lamotrigine plus clomipramine. The patient, a 59-year-old woman, was on a stable dose of clomipramine (225 mg/day) when she was started on lamotrigine (up to 150 mg/day). After 10 weeks of this treatment, her clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 24 publications
0
29
0
1
Order By: Relevance
“…Preliminary case reports and case series showed that resistant OCD symptoms may benefit from adjunctive nonselective glutamatergic inhibitors such as riluzole, 6,8,9 topiramate, 10 and lamotrigine. 11,12 In preliminary study, memantine, a weak uncompetitive NMDA receptor (NMDAR) antagonist, proved to be efficacious as add-on treatment to resistant OCD. 13,14 Meanwhile, Greenberg et al 7 conducted a randomized trial using glycine, a co-agonist for the activation of NMDAR complex, 15,16 as adjunctive treatment for refractory OCD.…”
mentioning
confidence: 99%
“…Preliminary case reports and case series showed that resistant OCD symptoms may benefit from adjunctive nonselective glutamatergic inhibitors such as riluzole, 6,8,9 topiramate, 10 and lamotrigine. 11,12 In preliminary study, memantine, a weak uncompetitive NMDA receptor (NMDAR) antagonist, proved to be efficacious as add-on treatment to resistant OCD. 13,14 Meanwhile, Greenberg et al 7 conducted a randomized trial using glycine, a co-agonist for the activation of NMDAR complex, 15,16 as adjunctive treatment for refractory OCD.…”
mentioning
confidence: 99%
“…La lamotrigina ha mostrado eficacia al agregarse a un ISRS en pacientes resistentes de acuerdo a dos EADCCP (36,37), a un trabajo retrospectivo (38) y a reportes de casos (39,40). Asimismo, la adición de pregabalina es útil en pacientes con TOC resistente a la combinación de ISRS y antipsicóticos atípicos de acuerdo a un estudio abierto (41).…”
Section: Anticonvulsivantes / Estabilizadoresunclassified
“…15 Lamotrigine has been reported to be beneficial in some case reports, 16 but not in others. 17 Topiramate is an anticonvulsant with a novel chemical structure.…”
Section: 5-7mentioning
confidence: 99%